Interação entre as formigas parabióticas Camponotus femoratus (Fabricius, 1804) e Crematogaster levior Longino, 2003 com suas epífitas associadas e influência sobre a composição da assembleia de formigas da Amazônia Meridional - Vicente, Ricardo Eduardo (2016)
A remarkable mutualistic interactions between ants and plants found in tropical forests is known as Ants-Gardens (AGs). The association between Camponotus femoratus (Fabricius, 1804) (Formicinae) and Crematogaster levior Longino 2003 (Myrmicinae) is among the most commonly found in the Neotropics. In AGs of these two species of parabiotic ants some species of epiphytic phylogenetically distant are often found. So to be effective mutualist partner the ants need to recognize and respond to all the different volatile chemical compounds of all associated species. Moreover, it is possible that plant AGs have converged as chemical signals when attacked by herbivores. If this were true, the ants also recruit all species of AGs locally. Considering this, in addition to describing the composition and the frequency of epiphytic species associated with nests locally, in the first chapter we tested the hypotheses that 1) the ants recognize chemical stimuli issued by different plants that inhabit the AGs and 2) they can differentiate this chemical stimulus when compared to the volatiles from a abundant plant specie of the understory. We found that only Ca. femoratus responds to herbivory stimuli in their mutualist epiphytes and that his reaction is related to overall frequency of epiphytes. When exposed to the AGepiphytes Peperomia macrostachya (Piperaceae) and Codonanthe uleana (Gesneriaceae) leaves it was observed that the recruitment of Ca. femoratus workers was, on average, respectively 556% and 246% higher than control (paper strips). The number of ants recruited by Markea longiflora (Solanaceae) or by the understory plant Piper hispidum (Piperaceae) did not differ from piece of paper. Because of this strong relationship of parabiotic ants with their mutualist epiphytes that need light to grow, in the second chapter we have created hypotheses that 1) the canopy openness of forest gaps influence the presence of AGs, and, 2) larger gaps will have more nests and 3) increase in both the canopy openness and the gap size will increase the colony size in forest gaps. Furthermore, it is known that although the arboreal nest, parabiotic ants are found foraging in the soil and in the vegetation. Then, we also believe that 4) the parabiotic ants are most frequently sampled in the vegetation and 5) increasing complexity of the vegetation and the litter accumulated volume in the soil increase the foraging of these ants in vegetation and ground, respectively, and the increase in canopy openness increases the activity of the two species in both strata. The presence and number Ants-Gardens, as colony size, was affected by the location, but not for the canopy openness. However, there was no difference in utilization of vertical strata by Ca. femoratus or by Cr. levior. On the other hand, the frequency of Ca. femoratus on the ground decreases with the canopy openness but is not affected by the complexity of the vegetation. In the frequency of Cr. levior on the ground also decrease with increasing the canopy openness. But, as opposed to Ca. femoratus, Cr. levior also shown to be influenced by the complexity of vegetation with a reduction in the frequency of workers that foraging on the ground with the increase of complexity in the vegetation. But not the complexity and canopy openness influence the foraging frequency of these ants in the understory. As these abundant species are considered dominant behaviorally, in Chapter 3, we investigated their impact on soil and vegetation ant communities separately. In this chapter in addition to investigating the effect of parabiotic ants in abundance, richness and community composition in both strata separately, we assessed whether they affected different components of beta diversity (turnover and nesting). Still, we assess which species are indicators of its presence or absence.